2004
DOI: 10.1063/1.1771461
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of thermally stable TiO2-terminated SrTiO3(100) substrate surfaces

Abstract: We have examined the thermal stability of TiO2-terminated SrTiO3(100) surfaces obtained by buffered HF etching and widely used as substrates for oxide film growth. In situ coaxial impact-collision ion scattering spectroscopy was used to measure the composition of the terminating atomic layer at temperatures up to 1000°C, simulating a broad range of thin-film growth conditions. The TiO2 termination of a nonannealed but HF-etched surface was found to start collapsing at temperatures as low as 300°C regardless of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 18 publications
5
74
0
1
Order By: Relevance
“…thick STO film. Such an annealing promotes the migration of surface species to the step edges, 32,33 and is routinely used as a complementary step after the buffered HF (BHF) etching to obtain the atomically flat TiO 2 termination with sharp unit-cell step edges. Since a long high-temperature anneal may also promote SrO segregation on the STO surface, 34 we keep our annealing time below 2 h. Figures 3(g) and 3(h) illustrate the topographic and friction images after the annealing treatment.…”
Section: -3mentioning
confidence: 99%
“…thick STO film. Such an annealing promotes the migration of surface species to the step edges, 32,33 and is routinely used as a complementary step after the buffered HF (BHF) etching to obtain the atomically flat TiO 2 termination with sharp unit-cell step edges. Since a long high-temperature anneal may also promote SrO segregation on the STO surface, 34 we keep our annealing time below 2 h. Figures 3(g) and 3(h) illustrate the topographic and friction images after the annealing treatment.…”
Section: -3mentioning
confidence: 99%
“…The perfect nature of the substrate is aimed experimentally, through appropriate chemical preparations (see for example [114,115] and references therein for SrTiO 3 ), as it was showed that a vicinal substrate could be used to control the (poly)domain structure [116].…”
Section: Limitationsmentioning
confidence: 99%
“…15 In this scenario, the electric field effect results suggest that the charge profile at the same density can be different. On the other hand, if interface perfection is modified by the growth temperature, 41 then the same charge profile would generate a different electronic mobility.…”
mentioning
confidence: 99%